Weathering the storm. Fair-weather versus stormy-weather governance in the euro area - Jean Pisani-Ferry; André Sapir (Bruegel, 2009)
Jean Pisani-Ferry and André Sapir believe that the euro has proved attractive as a fair-weather currency for countries and investors well beyond its borders. But it still remains to be seen if its governance is strong enough for it to succeed as a stormy-weather currency. The authors already detect, howevever, that the crisis shows the euro-area governance system lacks some crucial properties: speed of reaction, policy discretion and centralised decision-making.
Keywords: 330; Euro; Europäische Wirtschafts- und Währungsunion; Führungsorganisation; Geldpolitik; Finanzmarktkrise; EU-Staaten